ENGLISH AS A GATEWAY TO GLOBAL MARKETS: A QUALITATIVE STUDY OF VANILLA BUYER OUTREACH - rahmatul khasanah; Yanti Rahayu; nuria mufidah (Universitas An Nuur, 2026)
English plays an important role in international business communication and provides opportunities for small businesses to access global markets. This qualitative exploratory case study investigates the role of English in international buyer outreach conducted by an Indonesian vanilla business owner. Data were collected from 22 outreach attempts targeting prospective buyers in Malaysia, Singapore, Brunei Darussalam, Saudi Arabia, the United Kingdom, Japan, and the United States. Additional data were obtained from buyer response records and local purchasing cases. Data were analyzed using the framework proposed by Miles, Huberman, and Saldaña. The findings indicate that English facilitated initial communication with prospective international buyers but did not always lead to business opportunities. Four themes emerged from the analysis: English as a gateway to international communication, positioning ambiguity, product-market compatibility, and trust and credibility. The findings suggest that successful buyer outreach depends not only on English proficiency but also on clear business positioning, product relevance, and trust-building strategies. This study contributes to the fields of English for Specific Purposes (ESP), business communication, and SME internationalization.